A transposable element insertion in APOB causes cholesterol deficiency in Holstein cattle. (13th January 2016) - Menzi, F.; Besuchet‐Schmutz, N.; Fragnière, M.; Hofstetter, S.; Jagannathan, V.; Mock, T.; Raemy, A.; Studer, E.; Mehinagic, K.; Regenscheit, N.; Meylan, M.; Schmitz‐Hsu, F.; et al.
Summary: Cholesterol deficiency, a new autosomal recessive inherited genetic defect in Holstein cattle, has been recently reported to have an influence on the rearing success of calves. The affected animals show unresponsive diarrhea accompanied by hypocholesterolemia and usually die within the first weeks or months of life. Here, we show that whole genome sequencing combined with the knowledge about the pedigree and inbreeding status of a livestock population facilitates the identification of the causative mutation. We resequenced the entire genomes of an affected calf and a healthy partially inbred male carrying one copy of the critical 2.24‐Mb chromosome 11 segment in its ancestral state and one copy of the same segment with the cholesterol deficiency mutation. We detected a single structural variant, homozygous in the affected case and heterozygous in the non‐affected carrier male. The genetic makeup of this key animal provides extremely strong support for the causality of this mutation. The mutation represents a 1.3kb insertion of a transposable LTR element (ERV2‐1) in the coding sequence of the APOB gene, which leads to truncated transcripts and aberrant splicing. This finding was further supported by RNA sequencing of the liver transcriptome of an affected calf. The encoded apolipoprotein B is an essential apolipoprotein on chylomicrons and low‐density lipoproteins, and therefore, the mutation represents a loss of function mutation similar to autosomal recessive inherited familial hypobetalipoproteinemia‐1 (FHBL1) in humans. Our findings provide a direct gene test to improve selection against this deleterious mutation in Holstein cattle.